14C AMS Dating of Wooden Cores from Historic Buildings for Archaeological and Dendrochronological Research in High Asia. - Scharf, Andreas; Bräuning, Achim; Kretschmer, Wolfgang; Wegner, B; Darragon, Frederique Martine (Radiocarbon, 2013)
We had the opportunity to collect valuable wooden core samples from historic monasteries, temples, and secular buildings in 4 regions of High Asia, namely Dolpo (Nepal), ancient Nyangpo, Gyalrong/Minyag, and Lhasa and surroundings (all on the Tibetan Plateau, China). Tree species collected for dating include Pinus wallichiana (Dolpo), Juniperus tibetica, Pinus densata, and several species of the genera Picea (spruce), Larix (larch), and Abies (fir) on the Tibetan Plateau, which could not always be determined to the species level due to the parallel occurrence of species of the same genus in these regions. Some of the wood samples were successfully dendro-dated with local tree-ring chronologies, but many could not, indicating a potentially higher age than the existing local chronologies. By accelerator mass spectrometry (AMS) dating and wiggle-matching 199 14C samples from 73 collected timbers, it was possible to date these wood samples with high precision, and important information about the possible time of construction of these important historic buildings was obtained for the first time. Floating chronologies of 14C-dated wood span the periods AD 650 to 900 in Dolpo and 200 BC to AD 420 on the Tibetan Plateau. Besides dating of the wood samples from these historic monuments, 14C AMS dating with wiggle-matching gives the opportunity to extend the range of the currently existing regional tree-ring chronologies for future environmental reconstructions on the Tibetan Plateau and the Himalayas.
Keywords: Dendrochronology; Radiocarbon

Beyond dating: Archeological wood as a source of information of environmental changes in High Asia - Bräuning, Achim; Scharf, Andreas; Kretschmer, Wolfgang; Burchardt, Iris (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 11: Proceedings of the DENDROSYMPOSIUM 2012 Scientific Technical Report STR13/05, GFZ Potsdam, 2013)

The development of a long pine (Pinus wallichiana) chronology from western Nepal from living trees and 14C-dated historic wood samples - Bräuning, Achim; Scharf, Andreas; Kretschmer, Wolfgang; Gierl, Stefanie; Leichmann, Katrin; Burchardt, Iris (TRACE - Tree Rings in Archaeology, Climatology and Ecology, Vol. 9: Proceedings of the DENDROSYMPOSIUM 2010 Scientific Technical Report STR 11/07, GFZ Potsdam, 2011)
UnivIS-Import:2017-12-18:Pub.2011.nat.dgeo.IG.LGIPDT.thedev